Inhibiting Factors for Learning PJOK Online Volleyball Material at Elementary School - Azizin, Irhas; Hasmyati; Asran (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to determine the factors that inhibit PJOK learning of volleyball material during the Covid-19 pandemic at MIS Al-Hikmah Gempolmanis, Lamongan Regency, East Java. This study employs a descriptive-quantitative approach, utilizing a survey method. The study's population consisted of 42 students from class IV at MIS Al-Hikmah Gempolmanis. The total sampling technique was used in this study. The instrument used was a questionnaire test with a validity of 0.964 and a reliability of 0.981. The data analysis technique used descriptive analysis, which was expressed in the form of a percentage. The results of the study showed that the inhibiting factors for learning PJOK volleyball material during the Covid-19 pandemic at MIS Al-Hikmah Gempolmanis, Sambeng District, Lamongan Regency were in the categories of